2014
DOI: 10.1111/gcb.12518
|View full text |Cite|
|
Sign up to set email alerts
|

Greenhouse gas budget (CO2, CH4and N2O) of intensively managed grassland following restoration

Abstract: The first full greenhouse gas (GHG) flux budget of an intensively managed grassland in Switzerland (Chamau) is presented. The three major trace gases, carbon dioxide (CO2), methane (CH4), and nitrous oxide (N2O) were measured with the eddy covariance (EC) technique. For CO2 concentrations, an open-path infrared gas analyzer was used, while N2O and CH4 concentrations were measured with a recently developed continuous-wave quantum cascade laser absorption spectrometer (QCLAS). We investigated the magnitude of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
102
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 61 publications
9
102
0
2
Order By: Relevance
“…4d). The repeating pattern of sign changes of NEP around grazing events is qualitatively similar to that shown by Merbold et al (2014) around harvests. Prior to grazing, daytime NEP was greater than 1 g C m −2 h −1 ; after grazing, daytime NEP became negative, typically for about three days, before returning to positive values.…”
Section: Nep and Et: Fluxes Annual Sums And Partitioningsupporting
confidence: 70%
See 3 more Smart Citations
“…4d). The repeating pattern of sign changes of NEP around grazing events is qualitatively similar to that shown by Merbold et al (2014) around harvests. Prior to grazing, daytime NEP was greater than 1 g C m −2 h −1 ; after grazing, daytime NEP became negative, typically for about three days, before returning to positive values.…”
Section: Nep and Et: Fluxes Annual Sums And Partitioningsupporting
confidence: 70%
“…6), indicated that the reduction of leaf area was followed by a drop and then a rise in production. This is typical of grassland sites with repeated grazing or harvest events (Wohlfahrt et al, 2008;Merbold et al, 2014). During the growing season, repeated defoliations kept the grass in a permanent juvenile state, which helped to maintain strong biomass growth throughout.…”
Section: Effects Of Management Practicesmentioning
confidence: 93%
See 2 more Smart Citations
“…The eddy-covariance (EC) technique gives long-term, continuous, and spatially integrated measurements, which can fully capture FN2O. Advances in technology for N2O analyzers has increased the 10 number of long-term N2O measurement campaigns using EC methods (Mishurov and Kiely, 2010;Molodovskaya et al, 2012;Merbold et al, 2014;Huang et al, 2014;Rannik et al, 2015;Shurpali et al, 2016;Wang et al, 2016). However, the application has been limited to sites with high-quality power or short-term deployment.…”
Section: Introductionmentioning
confidence: 99%